Genomic profiling and pathological assessment of malignant peripheral nerve sheath tumors - Qian Cui; Fen Zhang; Jian Liu; Jie Xu; Hongmei Wu; Fangping Xu; Qingling Zhang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Addressing the significant clinical challenges associated with managing malignant peripheral nerve sheath tumor (MPNST), this study focuses on the difficulties encountered in achieving accurate pathological diagnosis and the exploration of effective treatment options through genomic analysis. Methods The study included 20 patients with an initial pathological diagnosis of MPNST. Next-generation sequencing-based genomic analysis was conducted to assess the molecular features of MPNST, specifically looking for somatic mutations and actionable mutations. Results The genomic analysis resulted in diagnostic refinement or reassignment for 20% of the cases. Somatic mutations were predominantly enriched in the RTK/RAS pathway, accounting for 64.7% of the findings. Additionally, actionable mutations were identified in 70.6% of patients who had a confirmed diagnosis of MPNST. Notably, the study revealed the presence of altered genes that were absent in Western populations, suggesting potential ethnic differences and the opportunity for alternative treatment strategies. Furthermore, patients with CDKN2A mutations exhibited significantly shorter disease-free survival compared to those without such mutations, with median survival times of 6.08 months versus 14.3 months (p = 0.0038). Conclusion The findings emphasize the necessity of molecular testing for accurate diagnosis of MPNST, which can guide optimal therapeutic options and highlight the need for tailored treatment strategies considering the heterogeneity of pathological phenotypes and molecular features among patients.